Pre-service Mathematics Teacher Efficacy: Its Nature and Relationship to Teacher Concerns and Orientation. (Alberta Journal of Educational Research, 2014)
In a mixed method study, teacher efficacy and contributing theoretical constructs of teacher concerns and teacher orientation with Intermediate/Senior mathematics preservice teachers from two Ontario Faculties of Education are examined.  Data sources include a web-based questionnaire containing two teacher efficacy scales and short answer questions, and interviews with the preservice teachers.  The study identifies a relationship between teacher efficacy (TE) and teacher concerns and orientation, and how high TE relates to combinations of teacher concerns and orientations and low TE relates to particular and individual teacher concerns and orientations.  Future research and considerations for preservice mathematics teacher programs are offered. Cette étude à méthodologie mixte porte sur l’efficacité des enseignants et les modèles théoriques qui contribuent aux préoccupations et aux orientations des enseignants. La recherche a impliqué des stagiaires en mathématiques aux niveaux intermédiaire et sénior dans deux facultés d’éducation en Ontario. Les données proviennent d’un questionnaire en ligne comportant deux échelles qui évaluent l’efficacité des enseignants ainsi que des questions à réponses courtes, et des entrevues auprès des stagiaires. L’étude identifie un rapport entre l’efficacité des enseignants et leurs préoccupations et orientations, et démontre dans quelle mesure le niveau d’efficacité est lié à des préoccupations et des orientations particulières. On propose des éléments à prendre en compte et des facteurs de recherche à prendre en considération pour les programmes d’enseignement des mathématiques.